Fruit quality in strawberry (fragaria sp.) grown on colored plastic mulch (2011)
Use of mulch has morphogenetic effects on strawberry (Fragaria sp.) production. In the present study the effects of red, blue, and fruit quality were evaluated in a trial carried out at 2,500 m a.s.l. in central Colombia. Red mulch gave results similar or better to the black control for most factors. Foliar area, fresh fruit weight, and fruit length were highest with red mulch and lowest for silver. Silver mulch gave the lowest pH and dry fruit weight, and the lowest ratio of total soluble solids/titratable acidity, while black mulch gave the highest value in this ratio.Positive effects of red mulch are possibly due to the increased absorption of red and far-red light by phytochrome, which in turn influences enzymes associated with sweetness and flavor.The superior results of red mulch were not always statistically significant, but the present study indicates the potential value of further tests on the use of red mulch instead of black mulch. If it is definitively shown that red mulch provides for better yield and fruit quality, it will be important to expand and improve its manufacture and stabilize its color, which often fades under high altitude tropical conditions.